Ijma dalam Ijtima' Gerakan Politik dan Dakwah: Studi Kontekstualisasi Amar Ma’ruf Nahi Munkar - Kadriyah, S Maryamah (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2024)
This research stems from the importance of understanding the relationship between Islamic movement, politics, and the implementation of amar ma'ruf nahi munkar within the framework of the principle of ulama consultation (ijtima). This study aims to elucidate the implications of this relationship as well as the distinction between ijtima' and ijma as decision-making processes. The method employed is library research and document analysis. Findings indicate that the principle of consultation in the Quran provides a basis for the participation of scholars and even the general populace in decision-making concerning various matters pertaining to the community, including matters of state. Decisions resulting from the ijtima' process differ from the ijma in the context of Islamic jurisprudence (fiqh). While ijma represents the consensus of scholars recognized as authoritative in determining Islamic legal rulings binding upon the Muslim community, decisions arising from the ijtima' process are more akin to outcomes of deliberation and consensus within the context of specific, situational, and limited decisions applicable to specific groups.